PELATIHAN PENULISAN KARYA ILMIAH BAGI GURU-GURU SEKOLAH DASAR NEGERI 171 KULIM KECAMATAN TENAYAN RAYA KOTA PEKANBARU - Syamsidar, Raja; Yani, Juli (Aksara Public, 2017)
Community service is done entitled "Training of Scientific Writing for Primary School Teachers 171 Kulim Tenaga Raya District". Scientific work is a scientific work formed in writing. Community devotion done to elementary school teachers because during this time they become obstacles is to make scientific work that has become the main requirement in promotion. Therefore, the teachers feel burdened with the requirements of the government because of this dedication is done so that teachers SDN 171 Kulim can do promotion and responsible in carrying out their duties as teachers, especially for elementary school teachers who are found in Kulim Kecamatan Tenayan Raya. The expected result after the dedication is done is the teachers of SDN 171 Kulim Tenaga Raya District has the ability and comprehension in writing scientific papers.